Community structure of fish in urban and natural streams in the Central Amazon - Silva, Cláudia P. D. (Amazoniana, 1995)
A community of fish from the Quarenta stream were shown to have been affected by urban pollution (domestic drains and industrial effluents).
Keywords: Igarapé do Quarenta